2016
DOI: 10.1590/s1806-92902016000800005
|View full text |Cite
|
Sign up to set email alerts
|

In vitro free radicals scavenging activity and antioxidant capacity of solid-state fermented wheat bran and its potential modulation of antioxidative molecular targets in chicken PBMC

Abstract: -The purpose of this study was to demonstrate the in vitro free radical scavenging activity and antioxidant capacity in solid-state fermented wheat bran and its potential modulation of antioxidative molecular targets in chicken peripheral blood mononuclear cells (PBMC). After solid-state fermentation of wheat bran by white rot fungi for 12 d, the scavenging action of the fermented wheat bran extracts was 1, 1-diphenyl-2-picrylhydrazyl (DPPH), and the free radicals increased significantly, approximately 1.5-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Mushrooms have superb antioxidant capacities and can increase antioxidant capacity in animals [5]. Wang et al [5,34] indicated that mushroom compost can improve the antioxidant capacity of poultry whether in vivo or in vitro. Animal antioxidant systems can be classified as enzymatic or non-enzymatic systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mushrooms have superb antioxidant capacities and can increase antioxidant capacity in animals [5]. Wang et al [5,34] indicated that mushroom compost can improve the antioxidant capacity of poultry whether in vivo or in vitro. Animal antioxidant systems can be classified as enzymatic or non-enzymatic systems.…”
Section: Discussionmentioning
confidence: 99%
“…As a catalyst, HO-1 can indirectly reduce the harm caused by H 2 O 2 by cleaving hemoglobin into biliverdin [39]. Previous research determined that phenols have antioxidant capacities and will activate Nrf2 expression [40], therefore mushroom additives can improve the enzymatic antioxidant system and enhance animals' adaptability to oxidative stress [34]. In addition, as a phenolic compound, epigallocatechin (1.493 mg /g PWMC) can enhance the antioxidant capacity of animals by chelating metal ions or increasing antioxidant enzymes [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three experiments were conducted in this study, FRS in situ degradation, milking performance and rumen degradation of dairy goats fed FRS diet. Fistulated Holstein dry cows, Alpine lactating goats, and Alpine fistulated dry goats involved were raised in the for eight weeks in a dark room [15].…”
Section: Methodsmentioning
confidence: 99%
“…However, no difference was observed between birds treated with 10% wheat bran solid fermented by Trichoderma longibrachiatum (S1) and unfermented wheat bran group (control 2). Although wheat bran fermented by white rot fungi Pleurotus eryngii could hold the promise of antioxidant activity and its antioxidant capacity would be evaluated as free radical scavenging capacity (Wang et al, 2016). Concerning to (HI) test (immune response to New castle disease virus), results indicated that birds treated with 10% wheat bran fermented by Trichoderma longibrachiatum (S1) not significantly increased HI antibody response (256.0), when compared to control-1 treatment and unfermented wheat bran which recorded the same titre (256.0).…”
Section: Assessment Of the Performance Of Chicks Fed With Wheat Branmentioning
confidence: 99%